2004
DOI: 10.1212/01.wnl.0000130504.88404.c9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of delayed focal MR changes in the lateral hippocampus in transient global amnesia

Abstract: The study confirms the involvement of hippocampal parenchyma in the pathophysiology of TGA. The delayed detectability of the lesions may explain the incongruence of previous MR DWI studies in TGA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
210
2
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(235 citation statements)
references
References 28 publications
14
210
2
9
Order By: Relevance
“…This result concurred with the study by Sedlaczek et al, 9 in which the lesion-detection rate was 6% within 8 hours of onset and increased up to 84% at 48 hours after onset. The pathogenesis of TGA is uncertain, and various etiologic hypotheses have been proposed, including thromboembolism, 9,10 cerebral venous congestion induced by Valsalva-like activities, [18][19][20] and vasoconstriction caused by hyperventilation. 21 Whatever its etiology, several authors have suggested that delayed neuronal injury in the hippocampus is the cause of the delayed appearance of the lesions on DWI.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result concurred with the study by Sedlaczek et al, 9 in which the lesion-detection rate was 6% within 8 hours of onset and increased up to 84% at 48 hours after onset. The pathogenesis of TGA is uncertain, and various etiologic hypotheses have been proposed, including thromboembolism, 9,10 cerebral venous congestion induced by Valsalva-like activities, [18][19][20] and vasoconstriction caused by hyperventilation. 21 Whatever its etiology, several authors have suggested that delayed neuronal injury in the hippocampus is the cause of the delayed appearance of the lesions on DWI.…”
Section: Discussionsupporting
confidence: 93%
“…6 Recent diffusion-weighted imaging (DWI) studies have indicated the presence of focal hyperintensities involving the hippocampus in TGA. [7][8][9][10][11] The lesions detected by DWI are small and punctate (1-3 mm) and located within the lateral portion of the hippocampus. 9,11,12 Since Strupp et al 13 first detected hyperintense lesions in the hippocampus in TGA by using DWI, the frequency of lesions detected on DWI has been reported in a range of 0%-84%.…”
mentioning
confidence: 99%
See 3 more Smart Citations